Evaluation of the antimicrobial efficacy of Minthostachys verticillata essential oil and limonene against Streptococcus uberis strains isolated from bovine mastitis - Montironi, Ivana Dalila (2016)
Bovine mastitis is a disease that causes great economic losses per year, being Streptococcus uberis the main environmental pathogen involved. The aim of the present study was to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of Minthostachys verticillata essential oil and limonene for S. uberis strains isolated from bovine mastitis. In addition, the effect of MIC on biofilm formation was analyzed. MIC values for the essential oil ranged from 14.3 to 114.5 mg/ml (1.56-12.5% v/v) and MBC between 114.5 and 229 mg/ml (12.5-25% v/v). MICs for limonene ranged from 3.3 to 52.5 mg/ml (0.39-6.25% v/v) and MBC was 210 mg/ml (25% v/v). Both compounds showed antibacterial activity and affected the biofilm formation of most of the strains tested. In conclusion, these compounds could be used as an alternative and/or complementary therapy for bovine mastitis caused by S. uberis.